PERAN E-COMMERCE DALAM PERUBAHAN LINGKUNGAN PEMASARAN GLOBAL: SUATU SYSTEMATIC LITERATURE REVIEW - Girsang, Azarya Agra Vincent; Sinurat, Yohana Gloria; Marbun, Mayerlita; Lase, Lisbet Hotmaria; Saragih, Lenti Susanna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of e-commerce in transforming the global marketing environment. The article was prepared using a qualitative approach with the Systematic Literature Review (SLR) method on relevant publications from 2020 to 2024. The review process involved formulating research questions, searching and selecting literature, extracting data, coding themes, conducting narrative synthesis, and interpreting the findings. The results indicate that e-commerce acts as a catalyst for global marketing transformation through five main dimensions: market expansion, competitiveness improvement, operational efficiency, supply chain optimization, and the transformation of distribution channels and marketing strategies. Digital platforms enable firms and SMEs to reach cross-border consumers faster, at lower cost, and in a more measurable way. At the same time, the use of data, marketplaces, social media, and social commerce encourages marketing personalization and more interactive customer experiences. However, e-commerce adoption also faces several challenges, including digital infrastructure gaps, low digital literacy, complex cross-border trade regulations, cybersecurity risks, and intensifying competition. This study confirms that e-commerce is not merely a transaction channel, but a strategic ecosystem that reshapes the global marketing structure. Therefore, businesses need to strengthen digital capabilities, adapt their marketing strategies, and manage risks in order to optimize opportunities in the digital economy. Keywords: e-commerce; global marketing; digital transformation; marketing strategy; systematic literature review